'Don't stop the mill': South African capital and agrarian change in Tanzania. Issue 5 (2nd September 2016) - Martiniello, Giuliano
Abstract: South African corporate agribusiness and large-scale commercial farmers have been major players in the current acquisitions of large tracts of very fertile land in southern and eastern Africa through massive investments in large-scale commercial farming, food processing, the production of biofuels and eco-tourism. By emphasising the significance of analysing the changing capital smallholder relationship in historical perspective, the paper explores continuity and change in the agrarian social structure and the land use dynamics of the Kilombero valley. It argues that smallholders are differentially and adversely integrated within agribusiness-led vertically organised agri-food chains consolidating and widening existing patterns of social inequality.